Assessment of bottom-cable interaction effects on mooring line dynamics - Chatjigeorgiou, IK; Mavrakos, SA (ASME, Fairfield, NJ, United States, 1998)
The paper presents an efficient time domain solution method for the 2D mooring line dynamics that accurately accounts for the bottom-cable interaction effects. The dynamic model simulates both the horizontal and vertical motions of the cable's lower end. The developed numerical algorithm is based on the method of finite differences. The numerical predictions have been compared with existing numerical and experimental data concerning dynamic tensions and mooring line induced damping. Moreover, in order to highlight the importance of the accurate bottom-line interaction effects in predicting the dynamic behavior of a mooring line, excessive comparisons have been made with solution methods, often used in the past, that approximately accounts for the dynamics of the lifted-off cable's part at its touchdown region.